The effect of bottom sediment supplement on changes of soil properties and on the chemical composition of plants - Tarnawski, Marek; Baran, Agnieszka; Koniarz, Tomasz (Geology, Geophysics and Environment, 2016)
The aim of the study was to assess the effect of bottom sediments on the selected properties of the light soil and the content of trace elements in the plant test. The bottom sediments collected from the Besko reservoir was added to the soil in the amount of 5, 10, 30 and 50% of air-dried sediment in relation to dry soil mass. The pot experiment was conducted on a light soil with weak loamy sand grain size composition and slightly acid reaction, which was enriched by a supplement of bottom sediment. The test plant was maize, Bora c.v. An applied bottom deposit revealed in its composition a considerable share of clay fractions, alkaline reaction and low total heavy metal content, therefore it may be applied as an admixture to light soils to improve their productivity. The addition of sediment to light soil resulted to the improvement of soil indicators of acidification: increased soil pH and reduced the value of hydrolytic acidity, improved sorption properties of the soil. A not uniform effect of bottom sediment admixture on trace elements contents in maize was determined. The sediment added to the soil increased the contents of copper, nickel, chromium and, whereas decreased the contents of zinc and cadmium in shoots. No excess of the permissible content of metals in plants used as animals forage were fund in the maize biomass.